Description of the bacterial RNA polymerase inhibitor GE23077-producer Actinomadura sp. NRRL B-65521T as Actinomadura lepetitiana sp. nov. Issue 8 (23rd August 2020) - Dalmastri, Claudia; Gastaldo, Luciano; Berini, Francesca; Marinelli, Flavia; Marcone, Giorgia Letizia
Abstract : The filamentous actinomycete that produces the antibiotic GE23077 was isolated by the Lepetit Research Group from a soil sample collected in Thailand, and it was classified as a member of the genus Actinomadura on the basis of its morphology and cell-wall composition. Phylogenetic analysis based on 16S rRNA gene sequences indicated that this strain formed a distinct monophyletic line within the genus Actinomadura, and it was most closely related to Actinomadura bangladeshensis DSM 45347 T (99.31 % similarity) and Actinomadura mexicana DSM 44485 T (98.94 %). The GE23077-producing strain formed an extensively branched, non-fragmented vegetative mycelium; no pseudosporangia were formed and the arthrospores were organized in slightly twisted chains. The cell wall contained meso -2, 6-diaminopimelic acid and the diagnostic sugar was madurose. The predominant menaquinone was MK-9(H6 ), with minor amounts of MK-9(H8 ) and MK-9(H4 ). The diagnostic phospholipids were phosphatidylinositol and diphosphatidylglycerol. The major cellular fatty acids were C16 : 0 and tuberculostearic acid (10-methyloctadecanoic acid), followed by minor amounts of C18:1 ω9 c, C16:1 ω7 c and 10-methylheptadecanoic acid. The genomic DNA G+C content was 71.77 mol%. Significant differences in the morphological, chemotaxonomic and biochemical data, and the low DNA–DNA relatedness between the GE23077-producing strain and closely related type strains clearly demonstrate that it represents a novel species of the genus Actinomadura, for which the name Actinomadura lepetitiana sp. nov. is proposed. The type strain is NRRL B-65521 T (=LMG 31258 T =DSM 109019 T ).